2020
DOI: 10.1140/epjc/s10052-020-8030-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the nature of the QCD transition in relativistic collision of heavy nuclei with deep learning

Abstract: Using deep convolutional neural network (CNN), the nature of the QCD transition can be identified from the final-state pion spectra from hybrid model simulations of heavy-ion collisions that combines a viscous hydrodynamic model with a hadronic cascade "after-burner". Two different types of equations of state (EoS) of the medium are used in the hydrodynamic evolution. The resulting spectra in transverse momentum and azimuthal angle are used as the input data to train the neural network to distinguish different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 87 publications
1
60
0
Order By: Relevance
“…DL methods are reliable and accurate in identifying QCD transitions in heavy-ion collisions. However, as reported in [20], the performance depend largely on the fluctuation in the final state spectra. Therefore, if such a DL based EoS-meter is to be used on the direct output of a heavy ion experiment, an extensive analysis on the response of the DL model on additional uncertainties introduced by e.g.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…DL methods are reliable and accurate in identifying QCD transitions in heavy-ion collisions. However, as reported in [20], the performance depend largely on the fluctuation in the final state spectra. Therefore, if such a DL based EoS-meter is to be used on the direct output of a heavy ion experiment, an extensive analysis on the response of the DL model on additional uncertainties introduced by e.g.…”
Section: Introductionmentioning
confidence: 83%
“…The study performed on the hydrodynamic output showed an average prediction accuracy greater than 95%. A follow up study was presented in [20] where a hadronic cascade model was employed after hydrodynamic evolution in the simulations to achieve a realistic freeze-out as well as including the effect of having a finite number of measurable particles in single events. The hadronic cascade "after-burner" introduces uncertainties in the final state spectra due to resonance decays and hadron rescatterings.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the performance of trained CNN routine is very robust against initial state fluctuations and final state interactions, such as decays of resonances. However, similar to other applications of DL technique to high energy physics [22][23][24], the program has to decide between two discrete choices: calculations either with soft or stiff equation of state. In other words, this is a one-dimensional discrete space.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Review of possibilities of application of ML and DL methods to high energy physics can be found elsewhere [19][20][21]. Prominent results of application of DL to problems of high energy nuclear physics and heavy-ion collisions are described in [22][23][24].…”
Section: Jhep07(2020)133mentioning
confidence: 99%
“…Due to its hierarchical structure of artificial neural networks aiming at representation learning, DL now provides an effective tool for pattern recognition of complex nonlinear systems. In physics there were already a lot of application in areas including nuclear [1,2,3,4], particle [5,6,7] and condensed matter physics [8,9,10]. Along with its significant progress in phase transition identification for classical or quantum spin models [11], deep neural networks has also been considered in the context of lattice field theory numerical simulations [12,13].…”
Section: Introductionmentioning
confidence: 99%